(untitled) (Economic and Political Thought, 2019)
This article focuses on the process of spreading fake news on the Internet. Today, by means of the media, users are able to distribute and disseminate a range of alternative content. The article shows the changes and consequences that users of new media must face. As a result of the unprecedented development of technology and disinformation that is spreading thereby, the tendency to fix erroneous beliefs in society is becoming more and more visible. The Internet creates perfect conditions to give autonomous cells an opportunity to quickly exchange information and confirm their beliefs. While traditional media are subject to institutional control, in the case of social media communication possibilities seem unlimited as they are subject only to social control, which in turn translates into the amount of rippling pernicious content. Dynamic development of technological solutions directly affects the placement of disinformation in another dimension. Fake news has become such an important problem in the media and social discourse that initiatives have been taken in many countries to combat the spread of disinformation on the Web. The key element is, above all, building public awareness and identifying false messages and sources that publish ‘fake news’.